Recent insights into green extraction techniques as efficient methods for the extraction of bioactive components and essential oils from foods. Issue 1 (31st December 2023) - Majid, Ishrat; Khan, Shafat; Aladel, Alanoud; Dar, Aamir Hussain; Adnan, Mohd; Khan, Mohammad Idreesh; Mahgoub Awadelkareem, Amir; Ashraf, Syed Amir
ABSTRACT: The extraction of bioactive compounds from natural food sources through non-conventional novel methods is gaining popularity due to their numerous advantages over conventional methods. In this review article, various extraction methods such as conventional and non-conventional novel methods were discussed with emphasis on green extraction methods. The use of hybrid extraction techniques has an effective and novel method of extraction. The bioactive compounds extracted by such novel techniques have great potential in functional food market, as they are considered as safer. Additionally, with an increasing interest of consumers toward food product, these novel greener technologies would be safer since it has less chemical interference. The outcome of this review will give an idea for appropriate extraction process with better efficiency and eco-friendly, which could be beneficial for extraction industry. Further research is required to validate these green extraction techniques in terms of their safety, consumer acceptability, challenges, and legal feasibility.